2021
DOI: 10.3390/nu13072478
|View full text |Cite
|
Sign up to set email alerts
|

Gamification for the Improvement of Diet, Nutritional Habits, and Body Composition in Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Currently, one of the main public health problems among children and adolescents is poor adherence to healthy habits, leading to increasingly high rates of obesity and the comorbidities that accompany obesity. Early interventions are necessary, and among them, the use of gamification can be an effective method. The objective was to analyse the effect of game-based interventions (gamification) for improving nutritional habits, knowledge, and changes in body composition. A systematic review and meta-analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 71 publications
(101 reference statements)
2
40
0
7
Order By: Relevance
“…However, studies have shown that such gamification features do not result in significantly different amounts of weight loss at 3, 6, 9, or 12 months between adults who do and do not undergo such programs [ 52 , 53 ]. Similarly, a meta-analysis reported that gamification did not result in significant weight loss differences between children and adolescents who did and did not undergo gamification for weight loss, although those in the former group were found to have improved nutritional knowledge scores [ 54 ]. This suggests that although gamification may improve weight loss knowledge, user engagement, and intention toward health behavior change, it is insufficient to impact any actual weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that such gamification features do not result in significantly different amounts of weight loss at 3, 6, 9, or 12 months between adults who do and do not undergo such programs [ 52 , 53 ]. Similarly, a meta-analysis reported that gamification did not result in significant weight loss differences between children and adolescents who did and did not undergo gamification for weight loss, although those in the former group were found to have improved nutritional knowledge scores [ 54 ]. This suggests that although gamification may improve weight loss knowledge, user engagement, and intention toward health behavior change, it is insufficient to impact any actual weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the necessity of adopting policies and programs to promote healthy eating at school, which, according to FAO, is an essential element to foster healthy diets at school and has been previously shown to combat unhealthy food consumption [ 30 , 31 ]. In addition, previous studies suggested that healthy diets could be promoted through communication channels that are appealing to children and adolescents (e.g., social media and gamification), in order to reach broader population groups, and especially those who live with overweight and obesity [ 32 ]. For example, a recent systematic literature review and meta-analysis by Suleiman-Martos showed that gamification could be an effective method to improve knowledge of healthier nutritional habits in children and adolescents [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies suggested that healthy diets could be promoted through communication channels that are appealing to children and adolescents (e.g., social media and gamification), in order to reach broader population groups, and especially those who live with overweight and obesity [ 32 ]. For example, a recent systematic literature review and meta-analysis by Suleiman-Martos showed that gamification could be an effective method to improve knowledge of healthier nutritional habits in children and adolescents [ 32 ]. Moreover, the systematic literature review by Chau et al suggested that social media is a promising feature for nutrition interventions in adolescents [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that, in children and adolescents, the use of video game elements in the home environment contributes to improving the BMI and body weight [128], dietary behavior and nutritional knowledge [129], level of PA, daily caloric expenditure, self-esteem, interactions, and social support [130]. The using of tele-exercise and exergames spread ahead the COVID-19 outbreak, especially among children with pathologies such as cerebral palsy, bone cancer, and cystic fibrosis.…”
Section: Online Exercise: Benefits and Efficacymentioning
confidence: 99%